2021
DOI: 10.5433/1679-0359.2021v42n6p3107
|View full text |Cite
|
Sign up to set email alerts
|

Seed and seedling morphology of Bauhinia scandens L.

Abstract: Bauhinia scandens has potential importance as an ornamental and medicinal plant. Researchers have isolated and identified 1-O-alkylglycerol in the leaves of the B. scandens plant, and established antitumor properties using the Brine Shrimp toxicity test, an internationally accepted bioassay. Although this species has high potential, little is known about the viability of seedling production and the morphology of these plants, particularly in terms of seed characteristics and initial stages of germination. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Martins et al (2008) reported a higher occurrence of empty seeds in Ocimum gratissimum L. seeds, with no germination of empty seeds. Results obtained with Bauhinia scandens L. and Crotalaria juncea L. seeds showed that seeds with malformed embryos, depending on the severity and location of the affected tissues, may eventually originate normal seedlings, but with less development of the embryo parts (Arruda et al, 2016;Jeromini et al, 2021).…”
Section: Resultsmentioning
confidence: 98%
“…Martins et al (2008) reported a higher occurrence of empty seeds in Ocimum gratissimum L. seeds, with no germination of empty seeds. Results obtained with Bauhinia scandens L. and Crotalaria juncea L. seeds showed that seeds with malformed embryos, depending on the severity and location of the affected tissues, may eventually originate normal seedlings, but with less development of the embryo parts (Arruda et al, 2016;Jeromini et al, 2021).…”
Section: Resultsmentioning
confidence: 98%